My year in meals - Ray, Rachael (Atria non fiction original hardcover, 2012)
"MY YEAR IN MEALS will give fans a glimpse into Rachael's own kitchen diary--what she herself cooked for her family for one whole year. From everyday meals to complicated culinary feats and meals she ate while traveling, this book will offer a side of Rachael you've never seen before. Rachael has you covered for breakfast, lunch and dinner--from a Provence Frittata with Cheesy Ciabatta Bread, mouthwatering Lemon Pesto Spaghetti, Truffle Garganelli, to French Onion French Bread Pizza. And for the first time ever, Rachael's husband and manager John Cusimano will be contributing to the book with a section devoted to his personal delicious cocktail recipes including the Fruita de Bosca (featuring blackberries, agave syrup, and fresh mint), the Strawberry Velvet (featuring honey liqueur, strawberries and lime) and the Ginger Mule (featuring ginger beer, agave syrup and gin). The book will also include Rachael's personal photos of the food she cooked throughout the year"--